Patient factors that lead to presentation delay in breast cancer among Sri Lankan women: A cross-sectional study - Senavirathna, Jeewantha; Gavesha De Silva,; Yohan Chamara,; Gamage, Hasangi; Heiyanthuduwa WR,; Jeyakumaran N,; Maheeka Seneviwickrama,; Kanchana Wijesinghe, (Asian Journal of Medical Sciences, 2024)
Background: Breast cancer (BC) poses a significant public health concern as it is the most common cancer detected among women worldwide. Early detection and intervention are associated with better prognosis and survival. A primary reason for the rising mortality and morbidity in developing countries is the lack of patient education and practice early detection programs and presentation. Aims and Objectives: The main objective of this study is to evaluate the prevalence of delayed presentation and the factors lead to delay among BC patients in Sri Lanka. Materials and Methods: A descriptive cross-sectional study was conducted from January 01, 2023, to June 30, 2023 among women diagnosed with BC attending two selected state hospitals in Sri Lanka. All women with histological diagnosis of early, locally advanced, or metastatic BC attending for treatment were included and women with recurrent BC and concomitant other cancers were excluded. Presentation delay was defined as ≥3 months. The calculated sample size was 396. Results: About 47.5% of our study population (n=188) had a presentation delay of more than 3 months. The main reasons for the delay in presentation were, being unaware that BC is a major problem in Sri Lanka, difficulty in accessing healthcare, and not being able to find time due to family and social commitments. Women who had not been practicing self-breast examination had a significant association with presentation delay (OR=3.26, 95% CI - 0.090–0.362, P=0.001). The participants who were having a presentation delay were also more likely to be diagnosed with an advanced stage of cancer (OR=2.86, 95% CI - 2.573–3.153, P=0.000). Conclusion: Our study population depicts a good knowledge related to BC symptoms, risk factors, and early detection methods. However, very few are practicing them. There is also a significant delay of presentation due to various factors. Awareness and good practices would lead to early detection and diagnosis and improve overall survival.